Treatment with progestagen and PMSG to prevent prolonged anestrus in buffaloes - KUMAR, HARENDRA; BHOOSHAN, NEERU; PATRA, M K; YADAV, M C (The Indian Journal of Animal Sciences, 2010)
The trial was conducted under field conditions to study the effectiveness of a treatment with progestagen in combination with PMSG on estrus induction, prevention of prolonged anestrus and fertility in noncycling buffaloes. Non cycling buffaloes (72) with average of 120±17.6 days postpartum were randomly allotted to one of the following treatments: progestagen + PMSG (n =44), 250 mg of P Depot im daily for 5 days and 500 iu folligon on seventh day of initiation of treatment and control group (CG, n = 28) without hormonal treatment. The progestagen + PMSG group showed higher estrus and synchronization rates (59.1 and 36.4%) than CG (14.28 and 3.5%). Buffaloes receiving progestagen + PMSG had higher overall pregnancy rate than CG (45.5 vs 14.28%, respectively). The treatment-first service period and calving– conception interval was shorter in hormonal treated (8.8± 2.5 and 192.5 ±16.8 days) than CG (25.2 ±3.3 and 238.9±24.7 days), respectively. In conclusion, treatment with progestagen + PMSG at 120 days postpartum was effective to induce estrus, prevent prolonged anestrus and reduce the calving-conception interval, improving reproductive performance in buffaloes.